Pengabdian Berbasis Literasi Islami untuk Menumbuhkan Karakter Religius di Kelurahan Timbang Langkat - Muhammad Yazid Maulana; Abdurrahman Abdurrahman (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service activity aims to foster the religious character of the community in Timbang Langkat Village through an Islamic literacy program. This program is implemented as a form of contribution from the Real Work Lecture (KKN) students in strengthening religious values in the community by increasing interest in reading, understanding, and practicing Islamic teachings contextually. The activity method is carried out with an approach implemented through counseling, religious studies, group discussions, and relevant, good and correct worship guidance according to the sunnah. The results of the implementation of the activity show a sense of enthusiasm from the community in participating in the literacy activities carried out, as well as the emergence of positive changes in the religious nature and behavior of children and the surrounding community, such as increased awareness of worship, social concern, and enthusiasm for learning worship such as prayer and tilawah. In addition, this activity also fosters a sense of togetherness between students and the community in building an environment with an Islamic character. The continued impact of this activity is seen from the formation of small study groups that independently continue Islamic literacy activities after the program ends. Thus, this Islamic literacy-based community service has proven effective as a means of developing sustainable religious character in the community, while strengthening the synergy between the Muhammadiyah University of North Sumatra and the Timbang Langkat Village community in developing local potential based on Islamic values.